Notes on the Steiger–Lind (1980) Handout. Issue 6 (1st November 2016) - Steiger, James H.
Abstract : This note presents the original Steiger-Lind (1980) handout entitled, "Statistically-Based Tests for the Number of Common Factors", distributed to all in attendance at the talk given at the annual meeting of the Psychometric Society in Iowa City, Iowa.